Indole‐3‐acetate beta‐glucosyltransferase OsIAGLU regulates seed vigour through mediating crosstalk between auxin and abscisic acid in rice. Issue 9 (15th February 2020) - He, Yongqi; Zhao, Jia; Yang, Bin; Sun, Shan; Peng, Liling; Wang, Zhoufei
Summary: Seed vigour is an important trait for direct seeding in rice. In this study, indole‐3‐acetate beta‐glucosyltransferase OsIAGLU was cloned in rice, and its roles on seed vigour were mainly investigated. Disruption of OsIAGLU resulted in low seed vigour in rice. Quantitative RT‐PCR analysis showed that the expressions of OsIAGLU were relatively higher in the late developing and the early germinating seeds and were significantly induced by indole‐3‐acetic acid (IAA) and abscisic acid (ABA). Transcriptome analysis revealed that the IAA‐ and ABA‐related genes were involved in the OsIAGLU regulation of seed vigour in rice. The higher levels of free IAA and ABA were identified in germinating seeds of osiaglu mutants compared to wild‐type (WT) plants. When treated with exogenous IAA and ABA, the osiaglu mutants and WT plants showed sensitivity to ABA while not IAA, but the exogenous IAA amplified ABA‐induced reduction of seed vigour in rice. The continuously higher expressions of ABA‐INSENSITIVE 3 ( OsABI3 ) and OsABI5 occurred in germinating seeds of osiaglu mutants compared to WT plants. The regulation of seed vigour by OsIAGLU might be through modulating IAA and ABA levels to alert OsABIs expression in germinating seeds in rice. Based on analysis of single‐nucleotide polymorphism data of rice accessions, two haplotypes of OsIAGLU that positively correlated with seed vigour were identified in indica accessions. This study provides important insights into the roles of OsIAGLU on seed vigour and facilitates the practical use of OsIAGLU in rice breeding.